Pelatihan E-Learning Google Classroom di SMAIT Asy-Syukriyyah Cipondoh - Puji Catur Siswipraptini; Rosida Nur Aziza; Karina Djunaidi; Rahma Farah Ningrum; Abdurrasyid Abdurrasyid; Riki Ruli Siregar (Terang, 2019)
SMAIT Asy-Syukriyyah is a high school located in Cipondoh, about 12 km from STTPLN. This high school has started to implement the distance learning method via the Internet, or known as E-Learning, as a complement to the existing teaching and learning process. One of the obstacles faced by the school in organizing E-Learning is the lack of human resources. The ability of teachers and the number of teachers who use E-Learning are still limited, as well as the students abilities. Therefore, the PKM Team from STT PLN intends to hold training for new students so that these students know the benefits of E-Learning and get to know the basics of using Google Classroom, as an application for E-Learning chosen by the school. The training is divided into several classes, each of which contains approximately 20 students. Each student is given the opportunity to practice directly through a computer or smartphone. The total number of participants who took part in the training was 82 students. And from the questionnaire given, all stated that the training provided was useful ..